Factor Path Analysis of Health Literacy,Self-care Activities, Diabetic Knowledge and Self-efficacy to Glycosylated Hemoglobin Level in the Elderly with type 2 Diabetes - Kulprasutidilok, Akua; Prasertsom, Prapaporn; Kulprasutidilok, Poonnat (Journal of health and health management, 2022)
This research aimed to analyze factor path of health literacy, self-care activities, diabetic knowledge, and self-efficacy to glycosylated hemoglobin level in the elderly with type 2 diabetes mellitus (T2DM). The samples of this research consisted of 380 elderly people with type 2 diabetes, selected by using multi-stage random sampling. The research tools used to collect data were diabetic health literacy scale, summary of diabetic self-care activity scale, diabetic knowledge questionnaire, and the Diabetic management self-efficacy scale. The statistics used to analyze data were percentage, mean, standard deviation, and path analysis. The results were found that the factor path model was consistent with the empirical data (χ2=18.897, df = 7, χ2/df = 2.70, GFI= 0.986, CFI=0.974, AGFI =0.945, SRMR=0.022, RMSEA=0.05, P value = .06). The glycosylated hemoglobin level was directly influenced by health literacy, self-care activities and diabetic knowledge with the influenced sizes at -0.03, -0.03, and -0.09 respectively. Meanwhile, it was indirectly done by the same factors with the influenced sizes at -0.01, -0.002, and -0.009. The coefficient of prediction (R-SQUARE) of glycosylated hemoglobin level was at 0.013. This indicated that all variables could explain the variance of glycosylated hemoglobin level at 1.3 percentages.